2022
DOI: 10.1111/bjd.21794
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data on the effectiveness, safety and drug survival of dupilumab: an analysis from the TREATgermany registry

Abstract: This interim analysis from the atopic dermatitis registry TREATgermany shows robust long‐term efficacy, favourable safety and high persistence of dupilumab under real life conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…[12][13][14][15] The currently most widely used targeted immunomodulating drug for moderate-to-severe AD is the anti-IL-4RA-antibody dupilumab. 16 Multiple studies have shown that dupilumab treatment leads to clinical improvements 17 along with reductions of inflammatory cell infiltrates and proinflammatory cytokine and chemokine expression in lesions 18 and an enhanced skin barrier function with decreased transepidermal water loss (TEWL) and normalized epidermal lipid composition. [19][20][21][22][23][24] Likewise, an increased microbial diversity and decrease of S. aureus abundance during dupilumab treatment was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] The currently most widely used targeted immunomodulating drug for moderate-to-severe AD is the anti-IL-4RA-antibody dupilumab. 16 Multiple studies have shown that dupilumab treatment leads to clinical improvements 17 along with reductions of inflammatory cell infiltrates and proinflammatory cytokine and chemokine expression in lesions 18 and an enhanced skin barrier function with decreased transepidermal water loss (TEWL) and normalized epidermal lipid composition. [19][20][21][22][23][24] Likewise, an increased microbial diversity and decrease of S. aureus abundance during dupilumab treatment was reported.…”
Section: Introductionmentioning
confidence: 99%
“…An important strength of this study is the long-term follow-up of 4 years, which has not been performed in other studies, to the best of our knowledge [8][9][10][11][12]. Interestingly, the 3-year survival rate (87.6%) and 4year survival rates (87.6%) were the same in this study.…”
Section: Spekhorst Et Almentioning
confidence: 55%
“…South Korea has a high hospital density relative to its population, which makes healthcare centers accessible [13]. which may explain the high drug survival rate of dupilumab compared to other reports in Europe and the US [8][9][10][11][12]. Additionally, South Korea's national insurance standards for severe AD are demanding [14].…”
Section: Spekhorst Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these findings, there remains a need for extensive real-world data to comprehensively assess the efficacy and safety of dupilumab in PN. Additionally, novel drugs targeting Th2 polarization in PN have demonstrated encouraging outcomes, such as tralokinumab, an anti-IL-13 monoclonal antibody, which demonstrated a significant reduction in itch severity as early as week 4 in a case series of patients with a PN-like phenotype of AD [45,177]. antibody, which demonstrated a significant reduction in itch severity as early as week 4 in a case series of patients with a PN-like phenotype of AD [45,177].…”
mentioning
confidence: 99%